Dynamic screening and printing of single cells using a microfluidic chip with dual microvalves. Issue 7 (26th February 2020) - Chen, Chang; Xu, Dong; Bai, Siwei; Yu, Zhihang; Zhu, Yonggang; Xing, Xiao; Chen, Huaying
Abstract : Inoculation of single cells into separate chambers is one of the key requirements in single-cell analysis. Here we report a three-layer microfluidic platform integrated with dual-pneumatic valves for dynamic screening and printing of single cells. Abstract : Inoculation of single cells into separate culture chambers is one of the key requirements in single-cell analysis. This paper reports an innovative microfluidic chip integrating two pneumatic microvalves to screen and print single cells onto a well plate. The upper and lower size limits of cells can be dynamically controlled by regulating the deformation of two adjacent microvalves. Numerical simulations were employed to systematically study the influence of membrane dimensions and pressure on the deflection of a valve. A mathematical model was then modified to predict the size of cells captured by a microvalve at various pressures. The membrane deflection was further studied using confocal imaging. The critical pressure trapping beads of various sizes was experimentally determined. These experiments validated the accuracy of both numerical simulations and the mathematical model. Furthermore, single beads and endothelial cells with the desired size range were screened using dual valves and printed onto well plates with 100% efficiency. Viability studies suggested that the screening process had no significant impact on cells. This device enables dynamic regulation of both the lower and the upper size limits of cells for printing. It has significant application potential in inoculating cells with desired sizes for various fields such as clonal expansion, monoclonality development and single-cell genomic studies.